Supply Chain Management in Building Commissioning Process in Accordance with the Leadership in Energy & Environmental Design (LEED) – A Case Study of KSA Construction Industry. - Mohamed EssamShaawat; Mohamed Alyagoub (International Journal of Supply Chain Management, 2019)
The commissioning procedure is one of the most effective processes used to improve the performance of building systems and equipment, and the supply chain management in construction industry is the main issue in its performance. Coincidentally, the Leadership in Energy and Environmental Design (LEED) values have the same core objective as of commissioning that is enlightening the building performance. The aim of the current research is to evaluate the building commissioning process in accordance with the Leadership in Energy Environmental Design (LEED) requirements for the new construction projects from contractor’s point of view in order to measure changes needed and spot on the shortcomings in the process requirements during the life cycle of a project. The building commissioning process is a tool to ensure that all building systems have been designed, installed, tested and operated in accordance with the original design and project scope, which ultimately results in producing a better product for the owner and society. A field survey was conducted through a structured questionnaire including 21 commissioning authority contractors (CxA) who are specialized in building commissioning. SPSS has been used to analyze the data to present statistical measures. The research concluded that there are some contractors not complying with the building commissioning requirements steps process. The results of the data show that the most important requirements that have not adhered by the contractors during the life cycle of a project. Moreover, Performance in the extent and corroboration credit was similar for all owner types, whereas investors performed otherwise from companies and government agencies in the improved commissioning credit. Practitioners who identify these significances and differences are expected to be better placed to make sustainability-related decisions in building design and construction.